Acute Disseminated Encephalomyelitis: Clinical Series - Kabaku, Nimet; Kurt, Ayşegül Neşe Çitak (Fırat University, 2005)
Objectives: Acute disseminated encephalomyelitis is typically a monophasic, demyelinating disease of the central nervous system that predominantly affects children. The work was done to describe the epidemiologic, clinical, neuroimaging and laboratory features; treatmet and outcome in children with Acute disseminated encephalomyelitis. Materials and Methods: Ten children with acute disseminated encephalomyelitis were seen at the Firat University Pediatric Neurology Unit over a five year period (July 1999-June 2005). Diagnosis was based upon typical clinical features and characteristic findings on neuroimaging. Cerebrospinal fluid examination and other investigations were done, where appropriate, to rule out other causes of central nervous system disease. Results: Six children had a prodromal illness. The most common presenting symptoms were ataxia, dysarthria and seizures. All children had an abnormal neurological examination. In the first administration, only three patients had hyperintense signals on brain magnetic resonance imaging. All children were treated with methylprednisolone, one child with optic neuritis received both methylprednisolone and immunoglobulins Patients who had more than one relapse (n = 2) presented with new symptoms at each attack. Of 10 children, 80 % recovered completely, but the patients who had more than one relapse has severe disability (hemiparesis and optic atrophy). Conclusion: Although in the cases of acute disseminated encephalomyelitis complete clinical recovery is common, serious neurological complications are also seen in childhood The timing and duration of steroid treatment affects outcome. ©2005, Fırat Üniversitesi, Tıp Fakültesi

Amaç: Akut dissemine ensefalomyelit tipik olarak eş zamanlı, genellikle çocukları etkileyen santral sinir sisteminin demiyelinizan bir hastalığıdır. Çalışmada akut dissemine ensefalomyelitli çocukların epidemolojik, klinik, kranyal görüntüleme ve laboratuar özellikleri; tedavi ve sonuçlarının araştırılması amaçlandı. Gereç ve Yöntem: Fırat Üniversitesi Pediatrik nöroloji ünitesinde beş yıllık bir süre içinde akut dissemine ensefalomyelitli 10 çocuk izlendi (Ocak 1999-Mayıs 2005). Tanı, tipik klinik özelliklere ve kranyal görüntülemelerinde bulunan karakteristik bulgulara dayanmaktaydı. Merkezi sinir sistemi hastalığının diğer nedenlerini dışlamak için beyin omurilik sıvısı incelemeleri ve diğer tetkikler yapıldı. Bulgular: Altı çocukda prodromal hastalık vardı. En yaygın görülen semptomlar ataksi, konuşma bozukluğu ve nöbet idi. Tüm çocuklarda anormal nörolojik muayene bulguları vardı. İlk incelemede, beyin manyetik rezonans görüntülemede yalnızca üç çocuk hiperintens sinyallere sahipti. Tüm çocuklar metil prednizolon ile tedavi edildi, optik nöritli bir çocukda hem metil prednizolon hemde intravenöz immunglobulin uygulandı. Birden fazla atak geçiren hastalarda (n=2) her atakta yeni semptomlar görüldü. On çocuğun %80'i tamamen iyileşmesine karşın, birden fazla tekrarlayan hastalarda ciddi sekel vardı (hemiparezi ve optik atrofi). Sonuç: Akut dissemine ensefalomyelitli olgularda tam klinik iyileşme yaygın olmasına rağmen, çocukluklarda ciddi nörolojik kompikasyonlar da görülebilir. Steroid tedavisinin zamanlama ve süresi sonucu etkiler. ©2005, Fırat Üniversitesi, Tıp Fakültesi
Akut Dissemine Ensefalomyelit: Klinik Seri